Enzyme-Crosslinked Electrospun Fibrous Gelatin Hydrogel for Potential Soft Tissue Engineering - Nie, Kexin (Polymers (Basel), 2020)
Soft tissue engineering has been seeking ways to mimic the natural extracellular microenvironment that allows cells to migrate and proliferate to regenerate new tissue. Therefore, the reconstruction of soft tissue requires a scaffold possessing the extracellular matrix (ECM)-mimicking fibrous structure and elastic property, which affect the cell functions and tissue regeneration. Herein, an effective method for fabricating nanofibrous hydrogel for soft tissue engineering is demonstrated using gelatin–hydroxyphenylpropionic acid (Gel–HPA) by electrospinning and enzymatic crosslinking. Gel–HPA fibrous hydrogel was prepared by crosslinking the electrospun fibers in ethanol-water solution with an optimized concentration of horseradish peroxidase (HRP) and H(2)O(2). The prepared fibrous hydrogel held the soft and elastic mechanical property of hydrogels and the three-dimensional (3D) fibrous structure of electrospun fibers. It was proven that the hydrogel scaffolds were biocompatible, improving the cellular adhesion, spreading, and proliferation. Moreover, the fibrous hydrogel showed rapid biodegradability and promoted angiogenesis in vivo. Overall, this study represents a novel biomimetic approach to generate Gel–HPA fibrous hydrogel scaffolds which have excellent potential in soft tissue regeneration applications.